Causal effects of the fracking boom on long‐term resident workers. (22nd December 2020) - Winters, John V.; Cai, Zhengyu; Maguire, Karen; Sengupta, Shruti
Abstract: Horizontal drilling innovations revolutionized the U.S. oil and gas industry and facilitated a boom in production in the mid‐2000s in regions with shale and tight‐sands reservoirs. This paper examines the effects of the boom on individual employment and earnings within boom states. We account for endogenous migration decisions by using a novel instrument for oil and gas production in workers' state of residence. We find statistically significant and economically meaningful positive effects of the oil and gas boom for long‐term resident workers, those who were born in and reside in their home state.